THE EFFECT OF DOMESTIC VIOLENCE ON THE MENTAL HEALTH OF VICTIMS: A LEGAL AND SOCIOLOGICAL APPROACH TO ITS MANAGEMENT - kayla, Nadira; Amalia, Mia; Mulyana, Aji (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2025)
Domestic violence (DV) is a serious social issue that has a significant impact on the mental health of victims. The psychological impact of domestic violence can include post-traumatic stress disorder (PTSD), depression, anxiety, and various other mental health problems that can hinder the well-being and productivity of victims. Addressing domestic violence requires a comprehensive approach, involving both legal and sociological perspectives. The legal approach aims to protect victims through laws and regulations that regulate sanctions against perpetrators and protective measures for victims. Meanwhile, the sociological approach focuses on understanding the social factors that influence the occurrence of domestic violence, such as cultural norms, gender inequality, and economic conditions, as well as providing social support to assist victims in the recovery process. This research examines in depth the impact of domestic violence on the mental health of victims and evaluates the effectiveness of the application of legal and sociological approaches in handling it. The results of this study are expected to serve as a basis for strengthening policies and intervention programs that are more effective in supporting victim recovery and reducing the incidence of domestic violence in the community.